2006
DOI: 10.1021/es061018y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Redox Status in Three Different Forested Wetlands with Geochemical Data

Abstract: Biogeochemistry and regulation of redox processes in wetlands and especiallytheir source sink functions regarding sulfur, nitrogen, iron, and alkalinity are still poorly understood and become increasingly important in a world of global change. We investigated three forested wetlands within the Lehstenbach catchment (Fichtelgebirge, Northeastern Bavaria, Germany) differing in their degree of water saturation, vegetation, and availability of iron with stable sulfur analysis as well as geochemical analysis (iron,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Our study of a natural wetland soil is significant because the microbial-driven biogeochemistry of redox processes in wetlands, particularly source-sink cycling of sulfur, remains poorly understood and increasingly relevant as a result of global climate change and modification of near-surface soil chemistry by human inputs ͑e.g., Alewell et al, 2006͒. For example, microbial sulfate reduction under anaerobic conditions is coupled to source-sink cycling of iron and heavy metal contaminants in wetland soils.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of a natural wetland soil is significant because the microbial-driven biogeochemistry of redox processes in wetlands, particularly source-sink cycling of sulfur, remains poorly understood and increasingly relevant as a result of global climate change and modification of near-surface soil chemistry by human inputs ͑e.g., Alewell et al, 2006͒. For example, microbial sulfate reduction under anaerobic conditions is coupled to source-sink cycling of iron and heavy metal contaminants in wetland soils.…”
Section: Discussionmentioning
confidence: 99%
“…S9). Nevertheless, previous studies have demonstrated high levels of sulfate reducing activity in the wetlands of the catchment (Alewell et al, 2006;Knorr et al, 2009), and sulfhydryl groups could thus form through reaction between sulfide and organic matter (Einsiedl et al, 2008;Hoffmann et al, 2012). Sorption of arsenic to iron (oxy)hydroxide colloids is important in soil systems (La Force et al, 2000;Blodau et al, 2008;Dousova et al, 2012;Langner et al, 2012) and has been extensively studied in the laboratory (Dixit and Hering, 2003;Bauer and Blodau, 2009;Sharma et al, 2010).…”
Section: Tablementioning
confidence: 99%
“…Within wetlands, microorganisms play an important role in transformations of heavy metals and metalloids via direct or indirect oxidation/reduction within the aquatic ecosystems (Alewell et al 2006;Dedysh et al 1998). In turn, the microbial transformations could lead the detoxification of pollutant elements such as arsenic, from anthropogenic sources D'Angelo and Reddy 1999;Mukhopadhyay et al 2002;White and Metcalf 2004).…”
Section: Introductionmentioning
confidence: 99%